Do surgery journals insist on reporting by CONSORT and PRISMA? A follow-up survey of 'instructions to authors'. Issue 1 (March 2015) - Smith, Tanya A.; Kulatilake, Priyantha; Brown, Lucy J.; Wigley, James; Hameed, Waseem; Shantikumar, Saran
Abstract: Aims: Guidance has been published on how best to report randomised controlled trials (Consolidated Standards of Reporting Trials - CONSORT) and systematic reviews (Preferred Reporting Items for Systematic Reviews and Meta-analysis - PRISMA). In 2011, we reported a low rate of enforcement by surgery journals for submitted manuscripts to conform to these guidelines. The aim of this follow-up study is to establish whether there has been any improvement. Methods: We studied the 134 surgery journals indexed in the Journal Citation Report . The 'Instructions to Authors' were scrutinised for inclusion of the following guidance: CONSORT, PRISMA, clinical trial registration and systematic review registration. Results: Compared to 2011, there has been an improvement in the endorsement of reporting guidance in journals' 'Instructions to Authors' in 2014, as follows: trial registration (42% vs 33%), CONSORT (42% vs 30%) and PRISMA (19% vs 10%, all p  < 0.001). As in 2011, journals with a higher impact were more likely to adopt trial registration ( p  < 0.001), CONSORT ( p  < 0.001) and PRISMA ( p  = 0.002). Journals with editorial offices in the UK were more likely to endorse guidance compared to those outside the UK ( p  < 0.05). Only one journal mentioned registration for systematic reviews. Conclusions: Surgery journals are presently more likely to require submitted manuscripts to follow published reporting guidance compared to three years ago. However, overall concordance rates are still low, and an improvement is required to help enhance the quality of reporting – and ultimately the conduct – of randomised control trials and systematic reviews in surgery. Highlights: There has been an improvement in the endorsement of reporting guidance in surgery journals' instructions to authors. Higher impact journals are more likely to require trial registration and adherence to CONSORT and PRISMA. There is still scope to improve the quality of reporting in surgery journals.